Global Sourcing of Heterogeneous Firms: Theory and Evidence - Wilhelm Kohler; Marcel Smolka (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper investigates the role of firm productivity in drawing firm boundaries in global sourcing. Our analysis focuses on how productivity affects the allocation of ownership rights between the headquarter of a firm and an intermediate input supplier (vertical integration vs. outsourcing), as well as the location of intermediate input production (offshore vs. domestic). Unlike previous work, we allow for a fully flexible productivity effect with varying magnitude and sign across different industries. Our estimation strategy is motivated by the canonical economic model of sourcing due to Antràs & Helpman (2004). This model invokes the property rights theory of the firm in order to pin down firm boundaries as the outcome of an interaction between firm heterogeneity and the industry's sourcing intensity (i.e. the importance of inputs sourced from suppliers relative to headquarter inputs). We demonstrate that, at the level of the firm, the model implies a productivity effect that varies not just in magnitude (and potentially non-monotonically), but also in sign with the sourcing intensity of the industry. To estimate the effects empirically, we use Spanish firm-level data from the Encuesta sobre Estrategias Empresariales (ESEE). We find a pattern of effects whereby productivity stimulates vertical integration in industries of low sourcing intensity, but favors outsourcing in industries of high sourcing intensity. Moreover, we find that productivity boosts offshoring throughout all industries, with the effect increasing monotonically in the sourcing intensity. Our results lend strong empirical support to the property rights view of the firm in the global economy.
Keywords: F12; F19; F23; L22; L23; 330; global sourcing; incomplete contracts; firm productivity; firm-level data